TANBIH AL-MASYI MENYOAL WAHDATUL WUJUD: KASUS ABDURRAUF SINGKEL DI ACEH ABAD 17 KARYA OMAN FATHURAHMAN (Review buku) - Zainuddin Abdullah (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2019)
Abdurrauf's approach in interpreting the teachings of wahdatul exists by combining the opinions of the two leaders of the Sufism; philosophical satire and practical saga. Ibn Arabi, Abdurrahman al-Jami and Ibn al-Farid can be attributed to the philosophical satire whose mystical views are quoted by Abdurrauf. While al-Ghazali, al-Junaid, al-Harawi, asy-Syadzili and Suhrawardi al-Baghdadi can be grouped together as characters of the Sufism who are also the backbone of his thinking. Oman Fathurrahman's study of Tanbih al-Masyi's text at least gives the impression that today's generation can see the text as Abdurrauf Singkel wrote it more than three hundred years ago. However, of course the research is complete if it is discussed Syatariyyah practices that contain a number of formulas or symbols of remembrance more intimately, thus rendering it more intact.